Management of Orofacial Pain in Elderly Patient with Hypertension : Case Report - Prijaryanti, Dorisna; Ayuningtyas, Nurina F.; Ernawati, Diah S.; Radithia, Desiana (Journal of Case Reports in Dental Medicine, 2020)
Orofacial pain is a pain that involves the face and oral cavity wich characterized by sharp pain, such as electric shock. This paper reported 67 years old female patient complained pain in the right gingiva, right palatum and right side of the face since 6 months ago. To defined diagnosis we need accuracy in anamnesis, clinical examination and supportive examination. The treatment of orofacial pain is vitamins B1, B6, B12 and multidisciplinary collaboration. Patients use drugs that are given routinely, and regulary control to neurologistÂ  and cardiologist then sorofacial pain begins to heal after 53 days.